INTOLERANCE TO PLATE DENTURES IN ORTHOPEDIC DENTISTRY - Muratova Saodat Kadirovna; Gafforova Hojaroy; Teshayev Shokhjakhon (Journal of new century innovations, 2024)
Annotation. After the introduction of base materials based on acrylic polymers into prosthetic dentistry, reports of various reactions to these materials appeared. Among the most common and important causes of acrylate tolerance are the following: mechanical anal injury caused by spikes during the preparation and processing of protons call; chemical-toxic and allergic effects of substances included in the composition of prostheses; non-physiological conditions under removable dentures; bacteriological effects of prosthetic plaque; diseases of internal organs (anemia, diabetes, atherosclerotic changes, etc.), hormonal disorders.